Study of Biological Indicators and Biochemical Changes Related to Gallstones Formation in Patients in Kirkuk City - Chrow Ahmed Khurshid; Amera Kamal Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study included (29) patients with gallstones who were visiting the New Kirkuk Hospital and whose condition was confirmed by conducting pathological examinations and ultrasound examination (sonar) in comparison to (29) healthy subjects.This study aimed on estimating of some chemical variables in blood serum, including measurement of total Bilirubin, direct and indirect Bilirubin. In addition, measuring the activities of Aspartate Aminotransferase (AST/GOT) and Alanine Aminotransferase (ALT/GPT), blood sugar, in relation to the percentage of patients consuming soft drinks, and the state of intestines and stool samples in both male and female for different age groups.A comparison was made between patients with gallstones and was confirmed to have jaundice and patients with gallstones who did not develop jaundice. A significant increase in blood sugar, the levels of total Bilirubin, direct and indirect Bilirubin, Aspartate Aminotransferase (AST/GOT) and Alanine Aminotransferase (ALT/GPT) was observed regardless to the patient’s gender, rate of soft drink consumption, and the bowel condition didn’t have effect in forming gallstone in comparison to healthy subjects.Comparison between patients with gallstones and healthy people has revealed the presence of significant differences in the bowel condition between two groups. Very high levels of total Bilirubin, direct and indirect Bilirubin, Aspartate Aminotransferase (AST/GOT) and Alanine Aminotransferase (ALT/GPT) in patients with lethargy of the intestine and indigestion. However, there were no significant differences in the percentage of blood sugar or the amount of soft drinks consumed between two groups. Gender has no effect on the results obtained.